Endoscopic and external approaches for orbital decompression: an analysis of trends from a U.S. perspective. Issue 8 (12th April 2018) - Svider, Peter F.; Arianpour, Khashayar; Nguyen, Brandon; Hsueh, Wayne D.; Langer, Paul D.; Eloy, Jean Anderson; Folbe, Adam J.
Abstract : Background: Although the endoscopic approach has been increasingly utilized for a variety of sinonasal and skull base pathologies, there has been little inquiry into its adoption in the surgical management of orbital disease. Our objective was to evaluate nationwide temporal and geographic trends in approaches for orbital decompression. Methods: Data available from the Centers for Medicare and Medicaid Services (CMS) were evaluated, focusing on the use of open and endoscopic approaches for orbital decompression (CPT codes 67414, 67445, 31292, and 31293) among Medicare beneficiaries over a 10‐year period. Regional data were also analyzed. Results: There were 8047 orbital decompressions billed to Medicare from 2007 to 2016. The number of external and endoscopic approaches increased by 73.0% and 29.2%, respectively, while the number of Medicare beneficiaries increased by 29.1%. Endoscopic decompression represented 23.5% of Medicare‐billed orbital decompressions in 2016 (221 of 939), down from 29.2% in 2007 (171 of 586). The South had the greatest proportion of decompressions utilizing an endoscopic approach (30.2%). Conclusion: There has not been a clear movement toward the endoscopic approach for orbital decompression, with modest growth when compared with external approaches. Potential explanations include the specialty‐exclusive nature of approaches, as well as a lack of consensus; the latter idea is further reinforced by geographic variation. High‐quality prospective trials may clarify the role of endoscopic approaches in these patients.